2019
DOI: 10.1017/s0950268819002127
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of community-acquired Staphylococcus aureus causing skin and soft tissue infections in a children's hospital in Shanghai, China

Abstract: Community-acquired Staphylococcus aureus is a major pathogen responsible for skin and soft tissue infections (SSTIs). This study aimed to investigate the prevalence and molecular characteristics of community-acquired S. aureus isolates recovered from paediatric patients with SSTIs in Shanghai, China. Between January 2015 and January 2018, 91 community-acquired S. aureus isolates were characterised by antibiotic susceptibility, multilocus sequence typing (ST), staphylococcal protein A gene (spa) type and virule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
3
16
2
Order By: Relevance
“…In consistent with some previous studies, 7 , 8 most of the OS-MRSA isolates investigated in this study belonged to SCCmec IV type, which was closely correlated with prevalent CA-MRSA strains, including ST59, ST15 and ST25 genotypes. 7 , 23 In contrast to a recent report from China, no dominant clone was found among 14 OS-MRSA isolates in this study and only ST22-t309 clone accounted for 14.29% (2/14). At the same time, ST22 was also reported to be a predominant clone among community-acquired infections.…”
Section: Discussioncontrasting
confidence: 99%
“…In consistent with some previous studies, 7 , 8 most of the OS-MRSA isolates investigated in this study belonged to SCCmec IV type, which was closely correlated with prevalent CA-MRSA strains, including ST59, ST15 and ST25 genotypes. 7 , 23 In contrast to a recent report from China, no dominant clone was found among 14 OS-MRSA isolates in this study and only ST22-t309 clone accounted for 14.29% (2/14). At the same time, ST22 was also reported to be a predominant clone among community-acquired infections.…”
Section: Discussioncontrasting
confidence: 99%
“…Meanwhile, similar to a previous Chinese study [35], we found SCCmec IV was the most dominant type in all isolates. Researchers [36] suggested the reason is that the combination of smaller size and lower cost on fitness may make SCCmec type IV the selectively favored element for transfer among all S. aureus isolates.…”
Section: Discussionsupporting
confidence: 90%
“…It is important to monitor the change in the distribution of SCC mec elements because in other countries, in particular the US, MRSA SCC mec –IV isolates reach 28%, China 61%, South Africa 48% and Japan 52.3%. 50–53 , 55 PVL is one of the main virulence factors that complicate the clinical features and the therapeutic approach, since prolonged treatment of MRSA infections, producing this toxin, with VAN can lead to therapeutic failure, so it is necessary to use combinations, such as LZD and CLI, to inhibit the production of PVL. 57 , 58 …”
Section: Discussionmentioning
confidence: 99%